2002
DOI: 10.1046/j.1471-6712.2002.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental phobic patients' view of dental anxiety and experiences in dental care: a qualitative study

Abstract: Dental phobic patients' view of dental anxiety and experiences in dental care: a qualitative study The aim of this study was to explore and describe dental phobic patients' perceptions of their dental fear and experiences in dental care. The study sample consisted of 18 participants (12 women), with a mean age of 39.4 years, selected consecutively from patients applying for treatment at a specialized dental fear clinic in Göteborg, Sweden. Dental fear, assessed by the Dental Anxiety Scale, showed score levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 44 publications
11
89
1
13
Order By: Relevance
“…A topic guide for the focus groups was developed based on a literature review [8,[14][15][16][17] and moderated by a clinical dentist with qualitative research training (MCW). As studies have shown that most dentally anxious people might be more afraid of root canal treatment (RCT) than other dental treatment [7,8] we opted to include questions relating to RCT specifically.…”
Section: Tool Developmentmentioning
confidence: 99%
“…A topic guide for the focus groups was developed based on a literature review [8,[14][15][16][17] and moderated by a clinical dentist with qualitative research training (MCW). As studies have shown that most dentally anxious people might be more afraid of root canal treatment (RCT) than other dental treatment [7,8] we opted to include questions relating to RCT specifically.…”
Section: Tool Developmentmentioning
confidence: 99%
“…Moreover, little is known about how (or even if) they feel the group has helped them with their anxiety or phobia or whether there are any disadvantages associated with accessing the group. It has also been noted that research into dental anxiety and phobia draws predominantly upon quantitative instruments, with a paucity of research employing in-depth qualitative methodologies, detailing the patient's own experience and perceptions of their dental anxiety or phobia 11,12 . Therefore, the primary aim of this study was to explore, using a qualitative methodology, the context through which dentally anxious individuals choose to access an online support group and their online experiences and to explore the extent to which online communication within the support group context is personal and meaningful to participants.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…8 Although many people associate a visit to the dentist with the onset of anxiety, a small minority suffer from dental phobia, which may present with symptoms such as hyperventilation. However, hyperventilation is not a regular occurrence under sedation.…”
Section: Resultsmentioning
confidence: 99%